Developing GESYA: a digital tool for enhancing emotional regulation in children with dyslexia - Agustina Twinky; Asri Wijiastuti; Pamuji Pamuji (Jurnal Konseling dan Pendidikan, 2026)
Children with dyslexia face not only reading difficulties but also challenges in emotional regulation, which are often underaddressed in digital learning interventions. This study aims to develop and evaluate the GESYA application, a digital tool designed to support emotional regulation in children with dyslexia. Using a Research and Development (R&D) approach, this study adopts the ADDIE model due to its systematic and iterative structure, which supports the design and refinement of educational digital media. The participants consisted of eight elementary school children with dyslexia from three learning and therapy centers in Sidoarjo and Surabaya. Data were collected through expert validation, practicality questionnaires, and a one-group pretest-posttest design using an adapted emotional regulation scale. The results indicate that the GESYA application achieved high validity (95% and 99.2%) and practicality (88%). A statistically significant improvement in emotional regulation was observed (p < 0.05). However, the magnitude of change was relatively modest, as reflected in the N-Gain score. These findings provide preliminary evidence of effectiveness, while the small sample size and study design limit broader generalization. Practically, the application supported children in recognizing and managing emotions through interactive and structured activities, indicating its potential as a supplementary tool in inclusive educational settings. In conclusion, while preliminary results demonstrate the feasibility and potential effectiveness of GESYA, further studies with larger samples are required to confirm its impact.